Nanotecnologia verde em uma perspectiva CTSA: análise de uma proposta didática WebQuest para a alfabetização científica na educação básica - Bernardinelli, Silvia (2014)
The objective of this work was to evaluate the teaching resource WebQuest and the topic of green nanotechnology in order to promote scientific and technological literacy in basic education. Specifically, we tried to identify the perceptions of students of nanotechnology; analyze the relationships among science, technology, environment and society (STES) established by the students when researching into nanotechnology; verify the learning of school content of chemistry by the students when it comes to nanocapsules of controlled release; and finally, check the acceptance of the WebQuest proposal by the students. The results showed that nanotechnology and the WebQuest resource are of great potential to promote scientific literacy in basic education. The students were guided to reflect on the relationships among science, technology, environment and society (STES); thus, developing the critical thought necessary to good citizenship. The approach also showed it is possible to relate basic school content of chemistry (pH, solubility, chemical equilibrium, equilibrium shift, etc.) to contents regarding nanotechnology, even though the students showed certain difficulty learning the school contents in order to understand the nanocapsules of controlled release. WebQuest, a teaching resource already successful for oriented online research activities, was also shown to be a very adequate tool to promote scientific literacy, as long as the task is oriented for such purpose.